PENGARUH SAFAR TERHADAP PERKEMBANGAN PERDAGANGAN INTERNASIOANL - Wijayanti, Anita; M.Kes, Hendrik (Manajemen Bisnis Syariah, 2010)
Safar according to language rules (etymology) drawn from the word Arab safaran "meaning visible or appeared, - plural form of words is asfaar. It is said like that because the word "safar" revealed the face, morality, character, and the original nature of a person, place, or things that have not been known previously when the air-traveling. While people who do safar (have a journey) is called musaf. Safar under the termsof  languages (etymology) means cutting travel distance, - the journey, and had left the village boundary. It is meant towards a certain place. The word safar according to syariat leaving a residence with intent to walk or to try on the way of Allah on earth. Safar by syariat divided into 5 types, namely: Safar which is haram, required,  sunnah, allowed (permissible), and  the makruh.By traveling to scavenge prosperity actually been happening since the first time man was created in the earth (ie. since the time of Prophet Adam  Prophet Ibrahim, as well as that experienced by other Prophets, such as  Prophet Moses, Prophet David, the Prophet Sulaiman, and others. By traveling has been done by several people at that time, among them the ancient Egyptians, Mesopotamia, the Saba (in Yemen), the island of Crete, Greece, Persia, and Rome.Simak Baca secara fonetik Simak Baca secara fonetik A journey to get  prosperity also been done since he has not become a prophet  the trade widely hailed by the friends when the jaahiliyyah and the aftermath of the Islamic developing.By the activities of traveling commerce, several countries / nations in Europe, they are Spanish, Dutch, Portuguese, English and French, managed to gain huge profits from strategic trading centers  in the areas of  his colony. Begin at mid of 20th century the term international trade that began with trade between countries, which led to the term globalization continues to grow until the 21st century today, as the development of communication and information. The historical facts data mentioned above indicate that the travel (safar) since the jaahiliyyah, Islam developed, medieval, and now generally been used as a measure in the search, get prosperity, and develop his prosperity which has been obtained, namely with air-traveling constantly, trying to find/ get a chance (especially with the trade), or deliver merchandise to a distant place or country Keywords: Safar, International Trade, Globalization